Flipped Classroom Elaborasi pada Google Classroom Sebagai Media Pembelajaran Bahasa di Era Industri 4.0 - Muhhamad Adam; Deni Wardana, Putri Arianita Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The accelerated advancement of technology and information in the Industrial Age 4.0, along with the paradigm shift in language teaching, affects all aspects of life, including education. Most people believe that conventional learning models cannot meet the increasingly diverse and dynamic needs of students. The subject of this research is the result of the implementation of the flipped classroom model on Google Classroom as a solution for Indonesian language learning in the Industrial 4.0 era. To collect data, this research uses case study and qualitative approaches. The results show that the flipped classroom model in Google Classroom improves students' motivation to learn, critical thinking skills, communication skills, and understanding of the material.